In Situ Liquid SAXS Studies on the Early Stage of Calcium Carbonate Formation. (23rd May 2019) - Mohammed, Ahmed S. A.; Carino, Agnese; Testino, Andrea; Andalibi, Mohammad Reza; Cervellino, Antonio
Abstract: Calcium carbonate is a model system to investigate the mechanism of solid formation by precipitation from solutions, and it is often considered in the debated classical and nonclassical nucleation mechanism. Despite the great scientific relevance of calcium carbonate in different scientific areas, little is known about the early stage of its formation. Therefore, contactless devices are designed that are capable of providing informative investigations on the early stages of the precipitation pathway of calcium carbonate in supersaturated solutions using classical scattering methods such as wide‐angle X‐ray scattering (WAXS) and small‐angle X‐ray scattering (SAXS) techniques. In particular, SAXS is exploited for investigating the size of entities formed from supersaturated solutions before the critical conditions for amorphous calcium carbonate (ACC) nucleation are attained. The saturation level is controlled and kept constant by mixing four diluted solutions (i.e., NaOH, CaCl2, NaHCO3, H2 O) at constant T and pH. The scattering data are collected on a liquid jet generated about 75 s after the mixing point. The data are modeled using parametric statistical models providing insight about the size distribution of denser matter in the liquid jet. Theoretical implications on the early stage of solid formation pathway are inferred. Abstract : Calcium carbonate clusters are investigated in situ by small‐angle X‐ray scattering (SAXS) using a liquid jet setup at constant pH, temperature, and saturation level. Saturation is kept below the critical value for amorphous calcium carbonate (ACC) formation. Highly hydrated small clusters (<2 nm) and large aggregates (superclusters, broad size distribution) are detected before ACC formation and even in undersaturated conditions.